Why is Price Discovery in Credit Default Swap Markets News-Specific? - Ian W. Marsh; Wolf Wagner (Tinbergen Institute, 2012)
We analyse daily lead-lag patterns in US equity and credit default swap (CDS) returns. We first document that equity returns robustly lead CDS returns. However, we find that the CDS-lag is due to common (and not firm-specific) news and arises predominantly in response to positive (instead of negative) equity market news. We provide an explanation for this news-specific price discovery based on dealers in the CDS market exploiting their informational advantage vis-à-vis institutional investors with hedging demands. In support of this explanation we find that the CDS-lag and its news-specificity are related to various firm-level proxies for hedging demand in the cross-section as well measures for economy-wide informational asymmetries over time.
Keywords: G1; G12; G14; 330; price discovery; hedging demand; CDS markets; equity markets; Spekulation; Asymmetrische Information; Finanzanalyse; Kreditderivat; Hedging; USA